Negotiating networked infrastructural inequalities: Governance, electricity access, and space in Rio de Janeiro. (March 2021) - Pilo', Francesca
In cities of the Global South, universal physical access to networked infrastructures, such as electricity and water, is often presented as enabling the reduction of social and spatial divisions. Whereas most of the discussions in these cities have focused on the obstacles to networked infrastructure expansion, little attention has been paid to the increased universalization of the physical electricity network in several Latin American, Caribbean, and Asian cities. This article unpacks the discussions around the modern infrastructural ideal and its local reshaping by building on the case of Rio de Janeiro, which has achieved universal grid electricity coverage, but where strong urban inequalities remain. By focusing on electricity grid management in favelas, this article analyzes how infrastructural inequalities emerge within the network. It suggests that, in order to understand how urban inequalities are reproduced or mitigated through networked infrastructure, it is important to consider the governance aspects of managing infrastructure. It develops this argument by focusing on the multi-level and heterogeneous spaces of infrastructure governance, including both national and institutionalized arenas, and local everyday practices between local actors on the ground. This analysis shows how networked infrastructural inequalities emerge from negotiation processes in which the fragmented nature of the urban environment is embedded. Through this analysis, the article contributes to current discussions on the urban geography and techno-politics of infrastructure by highlighting the negotiated nature of infrastructural inequalities beyond the modern infrastructural ideal.